Herpesvirus-associated diseases: biomarkers and advancements in clinical research - Lu Lu; Miao Fan; Xu Li; Wen Su; Xinyu Wang; Yuhua Xue; Lin Ma; KaiHu Yao; Ying Liu; Lei Jia; Dan Yu (Virology Journal)
Abstract Herpesviruses are responsible for a broad spectrum of diseases that impact various tissues and organs, which could lead to complex pathological manifestations and severe complications. These infections represent a significant burden on global public health. Increasing researches have focused on identifying biomarkers associated with herpesvirus-related diseases and the underlying mechanisms. Studies using clinical samples may better reflect the molecular basis of disease progression, offering new insights into the illustration of disease development. This review provides a comprehensive summary of recent progress in biomarker discovery across a range of disease conditions caused by herpesviruses, highlighting the latest experimental findings and clinical observations, with a particular focus on the potential applications of these biomarkers in clinical settings. Additionally, we discuss the major challenges in the current research of herpesvirus-associated diseases, intending to foster the discovery of novel diagnostic and therapeutic strategies and deepen our understanding of herpesvirus pathogenesis.